ANALISIS KUMPULAN PUISI TIRANI KARYA TAUFIQ ISMAIL DALAM PERSPEKTIF POLITIK KEKUASAAN ORDE LAMA - Widada, Dwi Masdi (J-PIPS (Jurnal Pendidikan Ilmu Pengetahuan Sosial), 2017)
Politics is a series of activities in society in a system that involves the process of determining and implementing a goal. In politics there is still a longing for order and peace. Politics is also used in exercising power. The tendency of power treats the dominance of the ruler in running his government. Poetry The work of Taufiq Ismail in a collection of tyrannical poems is a collection of protest poems. The poems were created in 1966. The poem can also be called a demonstration poem because in 1966 there was a student demonstration. At that time there was political turmoil that struck the country of Indonesia due to G 30 S / PKI. Students' opposition to political turmoil was colored by action taking to the streets. Students demonstrate against injustice. The year 1966 was a year of demonstration pioneered by students belonging to organizations opposed to arbitrary forms of government. They condemned the old order regime under the authority of Ir. Soekarno who has distorted a policy so that the people of Indonesia miserable. Keywords: Children's Literature, Values of Islamic teachings, Characters